The Extended Contact Hypothesis: A Meta-Analysis on 20 Years of Research. (May 2019) - Zhou, Shelly; Page-Gould, Elizabeth; Aron, Arthur; Moyer, Anne; Hewstone, Miles
According to the extended contact hypothesis, knowing that in-group members have cross-group friends improves attitudes toward this out-group. This meta-analysis covers the 20 years of research that currently exists on the extended contact hypothesis, and consists of 248 effect sizes from 115 studies. The aggregate relationship between extended contact and intergroup attitudes was r = .25, 95% confidence interval (CI) = [.22, .27], which reduced to r = .17, 95% CI = [.14, .19] after removing direct friendship's contribution; these results suggest that extended contact's hypothesized relationship to intergroup attitudes is small-to-medium and exists independently of direct friendship. This relationship was larger when extended contact was perceived versus actual, highlighting the importance of perception in extended contact. Current results on extended contact mostly resembled their direct friendship counterparts, suggesting similarity between these contact types. These unique insights about extended contact and its relationship with direct friendship should enrich and spur growth within this literature.